Temporal Trend of Tuberculosis in Wild Ungulates from Mediterranean Spain. (31st October 2013) - Vicente, J.; Barasona, J. A.; Acevedo, P.; Ruiz‐Fons, J. F.; Boadella, M.; Diez‐Delgado, I.; Beltran‐Beck, B.; González‐Barrio, D.; Queirós, J.; Montoro, V.; de la Fuente, J.; Gortazar, C.
Summary: Tuberculosis (TB), a chronic disease caused by infection with the Mycobacterium tuberculosis complex, is endemic in wild boar ( Sus scrofa ) and red deer ( Cervus elaphus ) in south‐central Spain. Understanding the temporal dynamics of this chronic infection requires long time series data collection over large areas. The aim of this paper was to identify the determinants of TB prevalence and severity in both species in Ciudad Real province, Spain, from 2000 to 2012. Study variables included management, population dynamics, and a range of geographical and climatological factors. The prevalence of TB in wild boar increased from 50% to 63% since the study commenced. This may be due to an increased hunting bag (a proxy for population abundance), which was correlated with TB infection rates. Low rainfall (a stochastic factor) was associated with higher individual risk of TB presence and progression, resulting in an increased proportion of severe cases of wild boar TB in dry years. This was probably a result of increased food restriction leading to a higher susceptibility to TB. In contrast, red deer TB showed an apparent stable trend, which may be a consequence of the species' higher and stable population size. Hunting management, characterized by fencing, was associated with a higher risk of TB in both wild boar and red deer, suggesting that intensive hunting management may have contributed to exacerbated TB figures. This difference was more marked in red deer than in wild boar, probably because fencing imposes less restriction on movement, population mixing and TB spread to wild boar than to deer. Our findings on TB dynamics are fundamental for assessing the impact of future disease‐control actions (e.g. field vaccination). Moreover, such control plans must operate in the long term and cover large areas.